One to Watch: A Germ Cell Tumor Arising in an Undescended Testicle in Rubinstein-Taybi Syndrome. Issue 6 (August 2016) - Butler, Grainne H.; Boyle, Michael; Lynch, Sally Ann; Ryan, Stephanie; McDermott, Michael; Capra, Michael
Abstract : A male preterm infant was born with dysmorphic features consistent with Rubinstein-Taybi syndrome (RTS). An undescended right testicle was noted on examination. At 5 months of age he developed a palpable right-sided abdominal mass and an elevated alpha-fetoprotein. Histology revealed a malignant germ cell neoplasm arising within the undescended testis. This is the first reported case of a germ cell tumor occurring in a pediatric patient with RTS. Urologic abnormalities occur in approximately 52% of RTS patients, of which cryptorchidism is the commonest. Given the frequency of undescended testes in this population, closer screening may be warranted.